EXPLORING THE IMPACT OF EARLY CHILDHOOD EXPERIENCES ON LONG-TERM EMOTIONAL DEVELOPMENT - Ayu Yuliani Sekriptini; Jamil Khan; Zara Ali (Yayasan Adra Karima Hubbi, 2026)
Early childhood is a critical developmental period in which emotional foundations are formed through interactions with caregivers and the surrounding environment. Experiences such as emotional support, caregiving consistency, and early relational security have been widely recognized as influential, yet their long-term impact on emotional development across later life stages remains insufficiently integrated within developmental research. This study aims to explore the influence of early childhood experiences on long-term emotional development, with particular attention to emotional regulation and psychological well-being. Data were collected using standardized caregiver-report instruments, observational measures, and age-appropriate emotional regulation and well-being scales. Descriptive and inferential statistical analyses were applied to examine developmental relationships over time. The findings reveal that early emotional support and caregiving consistency are significant predictors of long-term emotional regulation and psychological well-being. Individuals exposed to emotionally responsive and stable early environments demonstrated greater emotional resilience and adaptive emotional functioning in later stages of development. The study concludes that early childhood emotional experiences constitute a foundational determinant of long-term emotional development.